2015
DOI: 10.4315/0362-028x.jfp-14-288
|View full text |Cite
|
Sign up to set email alerts
|

Manure Source and Age Affect Survival of Zoonotic Pathogens during Aerobic Composting at Sublethal Temperatures

Abstract: Heat is the primary mechanism by which aerobic composting inactivates zoonotic bacterial pathogens residing within animal manures, but at sublethal temperatures, the time necessary to hold the compost materials to ensure pathogen inactivation is uncertain. To determine the influence of the type of nitrogen amendment on inactivation of Salmonella, Listeria monocytogenes, and Escherichia coli O157:H7 in compost mixtures stored at sublethal temperatures, specific variables investigated in these studies included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
1
4
0
1
Order By: Relevance
“…in ruminants and poultry, but horse samples tested positive only for L. monocytogenes. These findings are in agreement with other studies that also reported a wide range of foodborne pathogen prevalence which was associated with the animal manure source (e.g., species, season, diet and husbandry, intermittent shedding in natural reservoirs) and type of feedstocks/bedding used (Hutchison et al, 2004;Ingham et al, 2005;Jay et al, 2007;Sinton et al, 2007;Moriarty et al, 2011;Berry et al, 2013;Erickson et al, 2014Erickson et al, , 2015. Variation in management practices among the farms may reflect the spatial-temporal clustering of positive samples, highlighting the importance of surveying multiple farms and conducting multi-year studies.…”
Section: Pathogen Detection In Manuresupporting
confidence: 91%
“…in ruminants and poultry, but horse samples tested positive only for L. monocytogenes. These findings are in agreement with other studies that also reported a wide range of foodborne pathogen prevalence which was associated with the animal manure source (e.g., species, season, diet and husbandry, intermittent shedding in natural reservoirs) and type of feedstocks/bedding used (Hutchison et al, 2004;Ingham et al, 2005;Jay et al, 2007;Sinton et al, 2007;Moriarty et al, 2011;Berry et al, 2013;Erickson et al, 2014Erickson et al, , 2015. Variation in management practices among the farms may reflect the spatial-temporal clustering of positive samples, highlighting the importance of surveying multiple farms and conducting multi-year studies.…”
Section: Pathogen Detection In Manuresupporting
confidence: 91%
“…The factors such as feedstock type, carbon to nitrogen ratio, weather conditions, and mixing of the compost piles influence the temperature of compost piles and the quality of compost (Erickson et al, 2015;Sakthivadivu, Sivakumar, Kumar, & Natarajan, 2015;Yang et al, 2015). While composting swine manure with rice straw, Zhu (2007) observed that it took 5.1 hr and 3.6 hr to reach the bin temperature of 55 º C, when the C: N ratios were 20 and 25, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Shepherd, Liang, Jiang, Doyle & Ercikson (2007) reported that E. coli survived 14 days in dairy manure pile during composting [temperature of the pile was 50 º C]. The survival of E. coli in dairy cow manure was extended to 6 weeks when the composting pile temperature was kept constant at 30 ºC (Erickson, Smith, Jiang, Flitcroft, & Doyle, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(2.6×10 4 CFU) and a significant reduction in the viable counts of Listeria sp. (1.7×10 4 CFU) • Nitrogen was shown efficient for the inactivation of Salmonella , Listeria sp., and Escherichia coli in animal manure Goberna et al ( 2011 ) Erickson et al ( 2015 ) Dairy manure • Ammonia inactivated pathogens ( Salmonella spp., L. monocytogenes , and E. coli ) faster in fresh manure compared with aged manure Erickson et al ( 2014 ) Animal waste feedstock • Pathogens can be inactivated through heat and microbial competition during the composting process Gurtler et al ( 2018 ) …”
Section: Techniques For Effective Slaughterhouse Sh-biowaste Recyclingmentioning
confidence: 99%